Duchowy charakter zła: wokół myśli Fiodora Dostojewskiego - Posacki, Aleksander (Horyzonty Wychowania, 2017)
The author of the article, founding on the works of Fyodor Dostojewski, contemplates the nature of evil. He puts forward a thesis in which Dostojewski still presents it in spiritual categories.Forthesakeofexplanationheusestwoontologicalrealities:ofGod-manandofman-god.Heexplains at the same time thatevilconsistsinself-adorationofman,whichistherootofall evil.Thereforeself-adoration,asaspiritualactandfundamental option of man’s possible behaviours, has its essential components, which include man’s will and freedom. He explains that manchoosinghimselfinsteadofChristchoosesevil,createsevil and non-existence. Referring to Berdyaev, he adds thatevil cannot be explained without freedom. Evil appears on the ways of freedom. Without this connection with freedom there is noresponsibilityforevil.Withoutfreedom,Godwouldberesponsible for evil. Dostojewski, more deeply than anybody else, understood that evil is the child of freedom.Concludinghisresearch,theauthoronceagainreferstoBerdyaev, who wrote that „Dostojewski had a special attitude towards evil which can shock many people”. All the same, in Dostojewski’s worksevilis not aninevitable moment of the evolution of good. Evil is antinomic. An optimistic-evolutionary understanding of evil means rational removal of this antinomy. One can become rich through the experience of evil, obtain greater sharpness of awareness, but in order to achieve this one has to experience suffering, the tragedy of loss, unveil evil, throw it into hellfire, expiatefor his guilt. Evil is connected with suffering and should leadtoredemption.Dostojewskibelievedintheredemptiveand regenerating power of suffering.